Phagophobia: a case report - Ciyiltepe, Müzeyyen; Türkbay, Tümer (The Turkish Journal of Pediatrics, 2006)
Phagophobia is a form of psychogenic dysphagia. Although it is characterized by a fear and avoidance of swallowing food, fluids, or pills, physical examination and laboratory findings are normal. Here, we present a case of phagophobia, who at 13 years of age was brought to our hospital by his family because of his fear and avoidance of swallowing food and loss of weight. After psychiatric interview, the patient underwent an oral peripheral examination, stroboscopic laryngeal evaluation, the Bedside Swallow Evaluation, and the Modified Barium Swallow Study. His physical examination and all laboratory findings were normal. The management of this case included the combination of behavior therapy and a dysphagia management program. After approximately one month of utilizing these techniques, the case showed considerable improvement.